The development of a South African legal framework relating to patentable inventions made by employees - Tong, Lee-Ann (Department of Commercial Law, 2016)
This thesis answers the question of how South Africa ought to regulate ownership of patentable employee-inventions within the prevailing patent system. It is concerned with developing a South African legal regulatory framework for an optimal default allocation of ownership in patentable inventions made by employee-inventors in the private sector. It approaches this concern from the perspective that the law relating to ownership of employee-inventions should align with the purpose of patents as tools for encouraging private sector investment in technological innovation. This perspective is informed by a theoretical framework based on assumptions about, amongst other things, the role of patents as individual incentives, the nature of inventorship, and the likely incentive effect of a grant of a patent on employers' and employee-inventors' contributions to inventive activity. The core of the thesis is an analysis of the South African law relating to the allocation of ownership of patentable inventions between employers and employees to determine whether and how it supports the incentive function of the patent system. This includes a consideration of the ownership of intellectual property which may arise as a consequence of the inventive activity and which attract statutory protection in the form of copyright, industrial design rights, and plant breeders' rights. In the absence of international guidance and a dearth of sources about the South African approach, an examination of the British and American approaches provides insight into divergent legal regulatory responses to the same issue. A key conclusion is that the prevailing South African law does not provide for an efficient legal framework for the allocation of patent rights between employers and employees when reviewed against the purpose of the patent system in the innovation context. Based on this and other conclusions about the factors which ought to inform the regulation of the allocation, recommendations for a new legislative framework which is responsive to the purpose of patents as individual incentives, but which is also cognisant of the dynamics of the employment relationship, are made.